GEODYNAMIC SIGNIFICANCE OF THE JANATABAD PERIDOTITES AND ASSOCIATED CHROMITITES (S IRAN): IMPLICATIONS FOR SUBDUCTION INITIATION - Monsef, Reza; Monsef, Iman; Rahgoshay, Mohammad (Ofioliti, 2014)
The Janatabad peridotites are exposed in the Hajiabad-Esfandagheh Mélange Zone in the southern part of Iran. These peridotites are dominantly composed of harzburgites with small lenses and veins of chromitite ores surrounded by dunite sheaths. Harzburgites have accessory chromites characterized by moderate XCr of 0.59-0.61, and XMg of 0.52-0.58, resembling depleted mid-ocean ridge peridotites, supposed to have originated as the residue from a high degree of partial melting and MORB-like magma extraction at the inception of subduction. Dunites can be divided into two types: Type 1 dunite with moderate XCr of 0.53-0.62 and XMg of 0.48-0.53, and Type 2 dunite with high XCr of 0.63-0.67 and low XMg of 0.40-0.48. Two distinctive melts are required for the formation of these dunites: a MORB-like melt for the Type 1 dunite, and a transitional-like melt for the Type 2 dunite. These compositional variations from MORB to melts transitional between MORB and boninite are due to the hydrous fluids derived from the subducted oceanic slab into the overlying mantle wedge at the beginning of the down dip motion of the slab. Al-rich podiform chromitites, characterized by relatively low XCr of 0.53-0.54 and relatively high XMg of 0.60- 0.71, may have formed from MORB-like melts. In particular, the interaction between primitive MORB-like melts and depleted harzburgites produced Type 1 dunites and secondary silica-rich melts from which Al-rich chromitites crystallized. Type 2 dunites can be generated by the interaction between transitional-like melts and depleted harzburgites above a lithosphere in subsidence. Accordingly, it is inferred that the Janatabad peridotites formed by rifting of a Late Triassic to Early Jurassic embryonic ocean during subduction initiation of Neo-Tethyan lithosphere in an intra-oceanic environment.